Pharmacoeconomic aspects of the therapy for moderate and severe psoriatic arthritis - A. V. Rudakova; D. G. Tolkacheva; V. D. Sokolova (IRBIS LLC, 2021)
Objective: to perform cost-effectiveness analysis of the treatment for adult patients with psoriatic arthritis (PsA) with a Russian interleukin- 17А inhibitor netakimab in comparison with other biologic disease-modifying antirheumatic drugs (bDMARDs) and targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs) and to evaluate the influence of the inclusion of netakimab in the therapy for PsA on the budget of the Russian healthcare system.Material and methods. The evaluation of cost-effectiveness was performed from the position of the Russian healthcare system for patients with moderate and severe PsA. The evaluation was performed based on the results of the network meta-analysis of the randomized clinical studies. The criterion of clinical effectiveness included the changes in the condition of the joints by the criteria of the American College of Rheumatology (ACR20, ACR50, and ACR70) and changes in skin symptoms by the index of the prevalence and severity of psoriasis (PASI 75 and PASI 90) with a recalculation into quality-adjusted life-year (QALY). The time horizon of the cost-effectiveness analysis was 2 years. The calculation was based on the registered prices and VAT. If there was an original drug and a biosimilar registered on the pharmaceutical market, the calculation was based on the median of the registered prices. The budget impact analysis of the influence of netakimab inclusion in the therapy for patients with PsA was performed considering the structure of the prescription of bDMARDs and tsDMARDs that was determined in the pharmaco-epidemiological study conducted in the Russian Federation in 2020. The analysis was performed for patients that received medication by the scheme of reimbursement. The time horizon of the study was 3 years old.Results. In the base-case analysis, the cost-effectiveness ratio for netakimab was 1.210 mln rub/QALY (by 66.2-88.5% lower than in cases when comparison drugs were used). The budget impact analysis showed that the inclusion of netakimab in the therapy for PsA could reduce the costs by 376.60 mln rub (21.1%). Considering budget saving, the number of additional patients that can be treated will increase by 26.7% within 3 years.Conclusion. Netakimab is characterized by higher cost-effectiveness in comparison with other bDMARDs (adalimumab, golimumab, guselkumab, ixekizumab, infliximab, secukinumab, ustekinumab, certolizumab pegol, etanercept) and tsDMARDs (apremilast, tofacitinib) prescribed in the Russian Federation for patients with PsA. The inclusion of netakimab in the therapy for PsA will reduce the financial burden on the healthcare system.